2006
DOI: 10.1159/000091057
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Four Dentine Excavation Methods in Deciduous Teeth

Abstract: This in vitro study aimed to assess the speed and caries removal effectiveness of four different new and conventional dentine excavation methods. Eighty deciduous molars were assigned to four groups. Teeth were sectioned longitudinally through the lesion centre. Images of one half per tooth were captured by light microscope and confocal laser scanning microscopy (CLSM) to assess the caries extension. The halves were then reassembled and caries removed using round carbide bur (group 1), Er:YAG laser (group 2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
72
2
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 40 publications
6
72
2
7
Order By: Relevance
“…In contrast, the Er,Cr:YSGG laser, regardless of the applied energy density, resulted in an uncontrolled, random pattern, with deep over-prepared areas and wide under-prepared zones in the same cavity, in agreement with previous studies [7,35]. According to Celiberti et al, it is very difficult to give accurate guidelines for sound and hard dentin differentiation [35]. This issue is very prone to subjectivity and very dependent on the operator's perception and experience.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, the Er,Cr:YSGG laser, regardless of the applied energy density, resulted in an uncontrolled, random pattern, with deep over-prepared areas and wide under-prepared zones in the same cavity, in agreement with previous studies [7,35]. According to Celiberti et al, it is very difficult to give accurate guidelines for sound and hard dentin differentiation [35]. This issue is very prone to subjectivity and very dependent on the operator's perception and experience.…”
Section: Discussionsupporting
confidence: 90%
“…This finding suggests that ART removes more dental tissue than laser or bur treatment. Other have evaluated several methods of dentin caries removal and, unlike the results obtained in the present study, found that hand excavation is more conservative than the conventional bur technique [35,36]. The manual pressure during excavation and the objective of achieving a cavity with the least amount of infected tissue may have been responsible for this increased removal of dental tissue.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Some previous research on caries removal methods used natural lesions in human dentin 4,6,16,[17][18][19] . However, when natural lesions are used, it is difficult to standardize all of the variables that occur among samples 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Rotatory instruments, such as steel and carbide burs, are the most widely used caries-excavation methods 3 , and are considered the most efficient methods to remove caries in terms of time 16 . However, the use of burs tends to over-excavate dentin as the removal endpoint is based on a subjective visualtactile examination of dental tissues 16 .…”
Section: Discussionmentioning
confidence: 99%